Investigation of extracted bioactive compounds from local medicinal plant and theirs applications in preventive therapy from drugs addiction - عبيد وسام ،بن عمر رحيل (university of eloued جامعة الوادي, 2024)
تبحث هذه الدراسة في وجود القلويدات والتطبيقات العلاجية المحتملة في نبتتي الحرامي والعلندة ومن خلال تحليل نباتي وكيميائي للمستخلصات ، أظهرت نبتة الحرامي محتوى نوعي أعلى من القلويدات مقارنة بالعلندة ، وهو ما أكدته اختبارات ماير، فاجتر و دراجندورف أظهرت قلويدات الحرامى تأثيرات كبيرة مضادة للأكسدة ومضادة للميكروبات ومضادة لمرض السكر أكثر منها مقارنة ببيئة العلندة وتشير هذه النتائج بالإضافة إلى بعض الدراسات الى أن القلويدات الموجودة في هذه النباتات قد تحمل امكانية تطوير علاجات جديدة للإدمان ، مما يسلط الضوء على أهمية اجراء مزيد من البحوث في مركباتها النشطة بيولوجيا This dissertation investigates the presence and potential therapeutic applications of alkaloids in Lavender and Ephedra plants. Through a detailed botanical and chemical analysis, various extraction and testing methods were employed to identify the alkaloid presence in these plants. Lavender showed a higher qualitative content of alkaloids compared to Ephedra, confirmed by Mayer's, Wagner's, and Dragendorff's tests. Lavender's alkaloids exhibited significant antioxidant, antimicrobial, and antidiabetic effects more than Ephedra's study. These findings suggest that the alkaloids in these plants may hold potential for developing new treatments for addiction, highlighting the importance of further research into their bioactive compounds.
مدكرة ماستر كيمياء
Keywords: الحرامي العلندة، القلويدات الكيمياء النباتية الإمكانات العلاجية طرق الاستخلاص النشاطيات البيولوجية; Lavender; Ephedra; alkaloids; phytochemistry; therapeutic potential; extraction methods; biological activities